Performance-determining factors in biathlon prone shooting without physical stress - Köykkä, M.; Laaksonen, M. S.; Ihalainen, S.; Ruotsalainen, K.; Linnamo, V. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study investigated the most important factors determining biathlon prone shooting performance. 10 female and 16 male biathletes (age 19.9 ± 2.9 years) from the national teams of Finland and Vuokatti-Ruka Sports Academy performed 65 biathlon prone shooting shots without physical stress under laboratory conditions. Shooting performance and multiple aiming point trajectory variables were measured together with an analysis of triggering force. Based on the aiming point trajectory data principal component analysis, we identified four technical components in biathlon prone shooting: stability of hold, aiming accuracy, cleanness of triggering and timing of triggering. Multiple regression analysis further determined that cleanness of triggering, aiming accuracy and timing of triggering accounted for 80% of mean shooting performance (p < 0.001). Better stability of hold, aiming accuracy and cleanness of triggering were directly associated with better shooting performance (0.62 = |r| = 0.79, all p < 0.001). Better stability of hold measures were also associated with better cleanness of triggering, and higher pre-shot trigger force levels were associated with better stability of hold and cleanness of triggering. These results indicate that with both direct and indirect effects on performance, stability of hold seems to be a general prerequisite for successful biathlon shooting. The results also highlight the importance of aiming accuracy, cleanness and timing of triggering, along with a high pre-shot trigger force level. The variables identified in this study could be used to assess biathletes` performance in the most relevant shooting technical aspects to guide the emphasis of their shooting training.